The clinical perspective: How to personalise treatment in MS and how may biomarkers including imaging contribute to this? - Vermersch, P; Berger, T; Gold, R; Lukas, C; Rovira, A; Meesen, B; Chard, D; Comabella, M; Palace, J; Trojano, M (SAGE Publications, 2016)
Background: MS is a highly heterogeneous disease, both in its course and in its response to treatments. Effective biomarkers may help predict disability progression and monitor patients’ treatment responses. Objective: To focus on how biomarkers may contribute to treatment individualisation in MS patients. Methods: This review reflects the content of the presentations, polling results and discussions on the clinical perspective of MS during the first and second Pan-European MS Multi-stakeholder Colloquia in Brussels in May 2014 and May 2015. Results: In clinical practice, MRI measures play a significant role in the diagnosis and follow-up of patients with MS. Together with clinical markers, the rate of MRI-visible lesion accrual once a person with MS has started treatment may also help to predict subsequent treatment responsiveness. In addition, several molecular (immunological, genetic) biomarkers have been established that may also play a role in predictive models of MS relapses and progression. To reach personalised treatment decisions, estimates of disability progression and likely treatment response should be carefully considered alongside the risk of serious adverse events, together with the patient’s treatment expectations. Conclusion: Although biomarkers may be very useful for individualised decision making in MS, many are still research tools and need to be validated before implementation in clinical practice.